2016
DOI: 10.1118/1.4965046
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of output prediction models for a passively double‐scattered proton therapy system

Abstract: The first existing model has proven to be a successful predictor of output for our compact double-scattering proton therapy system. The new model performed comparably to the first model and showed better performance in some options due to a great degree of flexibility of a polynomial fit. Both models performed well using r. Either model with r thus can serve well as an output prediction calculator.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…The model can serve as the secondary verification of measured OFs. In this work we built three models based on machine learning methods to predict OFs and compared with the semi‐empirical modes developed for the MGH proton machine and later implemented for other proton machines . We have concluded that all the three machine learning models provided better results in terms of maximum absolute difference than previously developed semi‐empirical model, which has a large prediction error for the proton fields with a full range and full modulation width.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The model can serve as the secondary verification of measured OFs. In this work we built three models based on machine learning methods to predict OFs and compared with the semi‐empirical modes developed for the MGH proton machine and later implemented for other proton machines . We have concluded that all the three machine learning models provided better results in terms of maximum absolute difference than previously developed semi‐empirical model, which has a large prediction error for the proton fields with a full range and full modulation width.…”
Section: Discussionmentioning
confidence: 93%
“…Ferguson et al. implemented a similar model using different variations in the definition of R and M to predict OFs on limited data points for Mevion S250 …”
Section: Introductionmentioning
confidence: 99%
“…The modification was necessary for more accurate output prediction due to mismatch between nominal (vendor definition), theoretical (without straggling), and actually measured values of R and M . The derivation can be found in the appendix of our previous publication …”
Section: Methodsmentioning
confidence: 99%
“…All the option‐specific parameters for models B and C are fit by the Matlab curve fitting toolbox. Implementation of the analytical models in detail can be found in our previous publication …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation